UMAT YANG SADAR DAN AKTIF DALAM LITURGI - Paskalis Edwin I Nyoman Paska; Jhon Daeng Maeja (Jurnal Abdimas Bina Bangsa, 2024)
Before the Second Vatican Council, the Church did not involve the faithful in liturgical celebrations. The liturgy is dominated by the clergy. The Second Vatican Council renewed the liturgy. People must take an active part in the liturgy. This change has always been encouraged by the church to this day. The reality of that change has not been felt by all people. The parish of Mary Queen of Peace also still suffers from problems about the effectiveness of the faithful in the liturgy. The purpose of this activity is to realize the important role of the people in the liturgy. The methods used are guidance, socialization, direct practice and evaluation. The result of the activity was that the assistant priests received books and knowledge about the worship of the word. The youth and the whole congregation are led to be conscious and active in the liturgy